Risk factors associated with mortality, perinatal. Experience Hipolito Unanue Hospital in Tacna (1992-1997) - Ticona, Manuel (2015)
OBJECTIVES.- To establish the tendency of perinatal mortality rate and its components, late fetal and precocious neonatal deaths determine the maternal-perinate risk factors and causes associated with this mortality LOCATION: Tacna Hipolito Unanue Hospital. METHOD Review of the Perinatal Informatic System database (CLAP-OPS/OMS). RESULTS: From 15850 births during the period 1992-1997, 322 perinatal deaths were found corresponding to 228 late fetal deaths and 102 precocious neonatal deaths. Perinatal mortality rate was 20,5%, with a 14,4% late fetal and a 6,1% precocious neonatal. The main risk factors are Apgar at 1 and 5 minutes < 3 neonatal pathology (hyaline membrane, congenital alterations, infections), birth weight < 1500 g an gestational age < 37 weeks. The main causes of late fetal death were complications of the placenta, umbilical cord, and membranes; other disorders and the not well define, ones; hemorrhage and intra-uterine hypoxia and birth asphyxia. The most frequent causes of precocious neonatal death were illnesses of the respiratory system, congenital alterations, infections, neurological syndromes and cerebral insult. CONCLUSION: Perinatal mortality and its components tend to descend and the main risk facto depend almost exclusively on the neonate.